Mobilizações de registros de representação semiótica no estudo de trigonometria no triângulo retângulo com o auxílio do software GeoGebra - Berlanda, Juliane Carla (2017)
This research aimed to answer the following question: “How are the registers of semiotic representation mobilized in the approach of right triangle trigonometry with the help of the GeoGebra software, based on a sequence of activities with students of the 1st grade of high school?”. The sequence of activities was designed with an investigative conception, using the technological resource of GeoGebra, and was developed with a class of students of a public school in Erechim, in the state of Rio Grande do Sul, Brazil. This research is supported by the learning theory of registers of semiotic representation and constituted based on the Didactic Engineering methodology. Data collection was carried out through printed materials, files recorded with the software, and audio media containing the speeches of the students during the interventions. This material was analyzed considering the following categories: a) through mathematical experimentation and the consequent coordination of the various representations made possible by the dynamicity of GeoGebra resources, a program in which several semiotic representations were coordinated (natural language, figural, tabular, numerical, algebraic and symbolic), as well as the analysis of apprehensions (perceptual, discursive and operative); b) by proposing an exploratory approach in mathematics education, based on an environment of dynamic geometry and a sequence of activities with an investigative conception, in which the student‟s autonomy was verified in the accomplishment of the proposed activities, provided by the ease of manipulation of mathematical objects elaborated in GeoGebra; c) through the encouragement of mathematical communication in the classroom, through the preparation of written and verbal justifications, when the natural language register became evident, with the verification of the subjects‟ knowledge acquisition. In addition, the stages of Didactic Engineering, as well as its reflections, were recognized as fundamental for the development of this research and the elaboration of the sequence of activities. In the analysis of the results, it was verified that the students were able to acquire knowledge about the study of right triangle trigonometry.